2022
DOI: 10.1186/s12909-022-03354-2
|View full text |Cite
|
Sign up to set email alerts
|

Research-based education in undergraduate occupational therapy and physiotherapy education programmes: a scoping review

Abstract: Background In a research-based learning environment, students learn how to become critical thinkers and lifelong learners, and to generate discipline-enriching knowledge. Research training is important for all healthcare professionals and the integration of research in education can be one approach to improve evidence-based practice among future professionals. The purpose of this scoping review was to identify studies reporting on research-based education in undergraduate occupational therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The proposed way is through teaching and training a new generation of PTs, OTs, and clinical research professionals. This implies a new generation of faculty members, as concluded by Helgøy et al who recently indicated that “… research-based education should be increased among both faculty members and students ” ( 25 ). Similar conclusions had been reached by Pearce et al ( 26 ) who analyzed “Train-the-Trainers” courses for MDs and health professionals.…”
Section: The Need For Education Of New Professional Figuresmentioning
confidence: 99%
“…The proposed way is through teaching and training a new generation of PTs, OTs, and clinical research professionals. This implies a new generation of faculty members, as concluded by Helgøy et al who recently indicated that “… research-based education should be increased among both faculty members and students ” ( 25 ). Similar conclusions had been reached by Pearce et al ( 26 ) who analyzed “Train-the-Trainers” courses for MDs and health professionals.…”
Section: The Need For Education Of New Professional Figuresmentioning
confidence: 99%
“…What happens a lot is trying to carry out learning using research methods, as done by Al-Maktoumi et al In addition, studies on the development of RBL to find a suitable formula related to implementation in learning have also been carried out, such as research from Worapun (2021) to produce management learning based on RBL principles; Usmeldi (2017) The integration of RBL in learning has also been carried out by several researchers. Like Nuchwana (2012), McGill et al (2012, Brennan et al (2019), Rattanaprom (2019), Behrmann (2019), Westwell and Ingle (2020), Helgøy et al (2022), Marín (2021), Marín (2020), Kırıcı and Bakırcı (2021), Espinoza-Figueroa et al (2021). The integration of RBL almost resembles the results of RBL research as a method.…”
Section: Implementation Of Rblmentioning
confidence: 68%
“…Even if a continuous update and further development/training of knowledge during upcoming clinical practice are needed for optimal clinical application, the undergraduate program should provide a strong foundation for the conditions for taking in and interpreting research results and hence the scientific approach. As a scoping review concluded, students’ knowledge and understanding of scientific methodology are fundamental requirements for the ability to read and interpret scientific articles, which is also an important skill for clinical education [ 26 ]. The studies included in the scoping review highlight the importance of including scientific perspectives in undergraduate programs and developing students’ skills and competence.…”
Section: Discussionmentioning
confidence: 99%